전이성 피부 악성 흑색종에서 Pembrolizumab 치료 후 발생한 삼출망막박리 - 이소현(So Hyeon Lee); 최윤석(Yoon Seok Choi); 김진영(Jin Young Kim); 김유민(Yu Min Kim); 도재록(Jae Rock Do); 강용구(Yong Koo Kang); 박동호(Dong Ho Park); 신재필(Jae Pil Shin) (Daihan angwa haghoi jabji, 2024)
목적: 전이성 피부 악성 흑색종 환자에서 pembrolizumab을 사용한 보조항암화학요법 후 발생한 삼출망막박리 1예를 보고하고자 한다. 증례요약: 67세 여성이 우측 엄지의 악성 흑색종 및 액와부 전이로 진단받고 pembrolizumab 치료 후 3일 뒤 양안의 시력저하로 내원하였다. 최대교정시력은 우안 0.2, 좌안 0.7이었고 안압은 양안 14 mmHg였다. 안저검사에서 우안의 삼출망막박리 및 맥락막박리와양안의 맥락막망막주름이 보였다. 빛간섭단층촬영에서 우안의 삼출망막박리와 양안의 맥락막주름이 관찰되었다. Pembrolizumab을중단하고 경구 및 점안 스테로이드를 투약하였다. 1개월 뒤 시력은 우안 0.5, 좌안 0.8로 호전되었고 삼출망막박리와 맥락막박리는사라졌다. 3주 후 양안의 삼출망막박리가 재발하여 다시 경구 스테로이드와 사이클로스포린을 복용하였고 1개월 후 교정시력이 우안0.7, 좌안 0.8로 호전되었고, 양안의 삼출망막박리도 사라져 경구 스테로이드를 천천히 감량하며 치료 중이다. 결론: Pembrolizumab을 투여하는 환자에서 삼출망막박리가 발생할 수 있으며 약물 부작용에 대한 감별진단 및 치료가 필요할 것으로보인다. Purpose: To report a case of exudative retinal detachment after using pembrolizumab in a patient with metastatic cutaneous melanoma. Case summary: A 67-year-old woman, diagnosed with malignant melanoma of the right thumb and axillary metastasis, presented with bilateral visual disturbance 3 days after adjuvant chemotherapy with pembrolizumab. Her best corrected visual acuity was 0.2 in the right eye and 0.7 in the left, while the intraocular pressure was 14 mmHg in both eyes. Fundus examination showed serous retinal detachment and choroidal detachment in the right eye, as well as a chorioretinal folding in both eyes. Optical coherence tomography showed exudative retinal detachment and choroidal detachment in the right eye, along with choroidal folding in both eyes. The pembrolizumab was stopped immediately, and the patient began treatment with systemic and topical steroids. After 1 month, the visual acuity improved and there was no exudative retinal detachment or choroidal detachment. However, 3 weeks later, exudative retinal detachment recurred in both eyes. The patient started treatment with oral steroids and cyclosporine, which resulted in the resolution of the exudative retinal detachment after 1 month. Conclusions: Exudative retinal detachment may occur as a side effect of pembrolizumab treatment. Therefore, a differential diagnosis and appropriate treatment of ocular side effects are necessary. KCI Citation Count: 0